The Role of Foreign Ownership in Moderating Board Characteristics, Independent Directors, and Board of Commissioners on Bank Financial Performance in Indonesia - Serly Serly; Vindy Vanessa; Budi Harsono (Jurnal Akuntansi, 2026)
Purpose – The purpose of this study is to analyze the effect of board characteristics, including the presence of female directors, independent directors, and independent commissioners, on the financial performance of commercial banks listed on the Indonesia Stock Exchange (IDX), as well as to examine the role of foreign ownership in moderating the relationship between board characteristics and banking performance in Indonesia. Design/Methodology/Approach – This study uses a quantitative approach based on secondary data from the company's annual reports for the period 2019-2023. Findings – The results of the study show that the presence of female directors does not have a significant direct impact on bank financial performance, but has a more positive impact when they act as independent directors. In addition, independent commissioners have been shown to have a positive and significant influence on bank financial performance. These findings confirm that the effectiveness of the board of directors structure, particularly independence in supervision, plays an important role in improving banking performance and has strategic implications for strengthening financial sector governance in Indonesia. Research limitations/Implications – This study is limited to banks listed on the Indonesia Stock Exchange during the period 2019–2023 and uses relatively limited corporate governance variables and profitability indicators, so it does not fully reflect all factors that affect banking financial performance in Indonesia. Therefore, further research is recommended to expand the sample coverage and add other governance measures in order to gain a more comprehensive understanding of bank financial performance. Keywords: Bank Performance, Board of Directors, Foreign Ownership, Independent Commissioners, Independent Director